Design of Instrumentation in Detecting Blood Sugar Levels with Non-Invasive Technique Base on IoT (Internet of Things) - Agus Suprayitno, Eko; Setiawan, Akhmad; Dijaya, Rohman (International Journal of Engineering and Technology, 2018)
Diabetes mellitus is a disease with metabolic disorders that result from defects in insulin secretion, which results in hyperglycemia with impaired carbohydrates, fats and body proteins. Diabetes mellitus can be known by measuring blood sugar levels which are generally done by injuring the body (Invasive) for blood. Normal blood sugar values range from 70 - 200 mg/dL. For people with diabetes mellitus, checking blood sugar is an important thing to do to maintain their body condition. In this study made Instrumentation detection of blood sugar levels non-invasive (does not hurt the body). This study uses the MAX30100 sensor as a non-invasive measure of blood sugar levels, because to determine blood sugar levels is only done by attaching the index finger to the sensor, and does not hurt the fingers. The value of blood sugar levels in this instrumentation is displayed on LCD and Android smartphones. For serial communication, Instrumentation with Android smartphones is done with IoT (Internet Of Things) technology to make it easier for medical officers to monitor the condition of diabetics through remote Android smartphones. From the results of testing Non-invasive blood sugar detection instrumentation with industry standard blood sugar measurement (Invasive), the accuracy of blood sugar readings was 90.3% with a deviation of 1.2 - 39.6 mg/dL. Tests were carried out on 14 Normal patients and people with diabetes mellitus. Reading distance reading Non-invasive blood sugar detection instrumentation with an Android Smartphone can reach a distance of 823 Km as long as Instrumentation is connected to the internet. Tests have been carried out in several cities including Sidoarjo, North Jakarta, Sidoarjo-Lamongan, Sidoarjo-Kediri.Â